Exploring Learning Strategies and Emotional Responses among Child and Adult EFL Learners: A Qualitative StudyThis study investigates the English learning experiences of child and adult learners in Indonesia within the framework of Second Language Acquisit - Saadah Al Afiah; Lusiana Suciati Dewi (Teaching English and Language Learning English Journal, 2026)
This study investigates the English learning experiences of child and adult learners in Indonesia within the framework of Second Language Acquisition (SLA). Although age-related differences in language learning have been widely discussed, limited research has explored how learners from different age groups experience English learning in real classroom contexts. This study employed a qualitative approach involving semi-structured interviews with two elementary school students and two university students. Thematic analysis revealed two major findings. First, child learners predominantly relied on teacher-guided instruction and interactive classroom activities such as songs and videos, while adult learners demonstrated greater autonomy through the use of digital resources, films, and online materials. Second, both groups experienced positive emotions toward English learning; however, their motivational sources differed, with children driven by enjoyable activities and adults by academic and future-oriented goals. Despite this, both groups reported anxiety and fear of making mistakes, particularly in speaking. The findings highlight that English learning is shaped by the interaction of cognitive, affective, and contextual factors. This study emphasizes the importance of adapting English instruction to learners’ developmental and emotional needs.